PKM menulis paragraf deskriptif - Amra Ariyani; Sahril Sahril (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The aim of this activity is to train the students of English Education Study Program especially class C to write adescriptive essay through group work. The materials of this activity are the concepts of descriptive essay, parts of essay, makingan outline, writing a descriptive essay based on the outline, and giving correction and feedback towards the students’ writing. Theresults of this activity show that the students know and understand how to write a descriptive essay after making the outline ofthe essay although they are not used to writing a good essay and they still have lack of vocabulary. In addition, they becomefamiliar to work with their group to make the essay.